Asilyo panel dividers for improvised evacuation centers in Marikina City - Dalumpines, Angeli Blanca
Disasters continue to haunt the Filipino people every year hence, preparatory and recovery measures are needed for the safety of the public. Cites like Marikina are geared towards a systemic approach to providing solutions to these threats, especially with evacuation. Evacuation centers often cater to the informal and vulnerable settlers as they are at the most risk to natural calamities. however, several problems arise from these, including the mismanagement of evacuation centers. This thesis documents the integration of panel dividers in the proposed Marikina City flood evacuation ID plan in which Asilyo, multipurpose panel dividers, would be streamlined into the proposed new system to create an immediate and intermediate solution to mismanaged evacuation centers for the benefit of evacuees.